Heat stress and the chicken gastrointestinal microbiota: a systematic review - Chris Major Ncho (Journal of Animal Science and Biotechnology)
Abstract Heat stress (HS) has become a significant challenge for poultry farming due to an increase in global temperatures. Existing literature suggests that the health effects of HS in chickens are related to its impact on the gastrointestinal tract. While there is evidence of the detrimental consequences of HS on the gut structure, little is known about the effects of HS on the microbial population inhabiting this organ. Fortunately, recent advancements in "omics" technologies have made investigating the interaction between HS and the gut microbiota possible. Therefore, a systematic review was conducted to assess the effects of HS on chicken gut microbiota. In July 2024, a comprehensive literature search was performed across scientific repositories, including Scopus, PubMed, Science Direct, and Google Scholar. Eighteen studies met the eligibility criteria for inclusion and a qualitative synthesis of their results was conducted according to the PRISMA guidelines. Current evidence indicates that HS poses a significant challenge to the gastrointestinal system of chickens, resulting in a range of physiological reactions. These changes trigger fierce competition among beneficial microbial species for limited nutrients, promote microbial shifts from obligate to facultative anaerobes, and increase the abundance of microbial species with high resistance to elevated environmental temperatures. Furthermore, the proliferation of pathogens is exacerbated. Ultimately, gut microbiota profiling highlights changes in microbial diversity, alterations in the composition of microbial populations, disruptions in specific microbial functional pathways (tricarboxylic acid cycle, amino acid metabolism, antioxidant biosynthesis, and fatty acid degradation), and the breakdown of complex networks that govern microbial interactions. Understanding the complex relationship between HS and microbial shifts within the chicken gut can provide valuable insights for the development of sustainable mitigation strategies. Further research is needed to expand the current knowledge and employ more advanced literature synthesis techniques such as meta-analyses. Graphical Abstract